Three-dimensional analysis of mitochondrial crista ultrastructure in a patient with Leigh syndrome by in situ cryoelectron tomography - Siegmund, SE; Grassucci, R; Carter, SD; Barca, E; Farino, ZJ; Juanola-Falgarona, M; Zhang, P; Tanji, K; Hirano, M; Schon, EA; Frank, J; Freyberg, Z (Cell Press, 2018)
Mitochondrial diseases produce profound neurological dysfunction via mutations affecting mitochondrial energy production, including the relatively common Leigh syndrome (LS). We recently described an LS case caused by a pathogenic mutation in USMG5, encoding a small supernumerary subunit of mitochondrial ATP synthase. This protein is integral for ATP synthase dimerization, and patient fibroblasts revealed an almost total loss of ATP synthase dimers. Here, we utilize in situ cryoelectron tomography (cryo-ET) in a clinical case-control study of mitochondrial disease to directly study mitochondria within cultured fibroblasts from a patient with LS and a healthy human control subject. Through tomographic analysis of patient and control mitochondria, we find that loss of ATP synthase dimerization due to the pathogenic mutation causes profound disturbances of mitochondrial crista ultrastructure. Overall, this work supports the crucial role of ATP synthase in regulating crista architecture in the context of human disease.